Some Roxburgh Grave-Slabs and a Coped Stone at Ancrum - Craw, J Hewat (Proceedings of the Society of Antiquaries of Scotland, 1922)
A description of six grave slabs found before 1857 is reproduced along with the account of further stones made in the 18th century. One of these commemorated a Johanna Bullock. A coped grave-cover was found in the churchyard at Ancrum.